Psychological Assessment of Doctors Working in a Pandemic Condition in Dhaka Medical College Hospital - Mahmud, Imran; Azad, Khan Abul Kalam; Mamun, Abdullah Al; Hoque, Mohammad Mahfuzul; Mallik, Md Uzzwal; Md Moniruzzaman, -; Saha, Shukdeb; Mark, Sayeef Hossain Khan; Rahman, Md Mujibur (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: The outbreak of COVID-19 is taking an unprecedented mental toll on health workers worldwide. So it comes as no surprise that the mental well-being of health care workers of Bangladesh too is in serious jeopardy. This survey was aimed to assess the immediate psychological impact on doctors working in largest Covid-19 dedicated facility in Bangladesh, Dhaka Medical College Hospital. Methods: This cross sectional study was conducted in a single-centre with response received from participating doctors between 31st May to 3rd June, 2020. Mental health variables were assessed via the Athens Insomnia Scale (AIS) and Hospital Anxiety Depression Score (HADS). Results: We received 192 completed questionnaires (response rate, 64.43%) among whom around 50% of the participating doctors reportedly have depression and anxiety symptoms respectively. Among them 104 doctors (54.17%) responded to have insomnia. Around 56% of the responding subjects perceived the highly contagious nature of the SARS-CoV-2 as the most striking threat of COVID-19. Conclusion: Agonizing disease process, high death toll, highly contagious nature of the responsible virus is taking a serious mental toll on physicians in the background of their heightened concern about personal health and family health, scarcity in PPE and adequate hospital facility. Psychological protective measures implemented by the hospital could be helpful. J Bangladesh Coll Phys Surg 2020; 38(0): 50-55